Effectiveness of Ecoenzyme Mosquito Repellent Combination of Lime Peel And Papaya Leaf Based - Fitri, Wahyuni; Satria, Rijal (Jurnal Serambi Biologi, 2024)
Mosquitoes are vectors of various diseases in humans, namely filariasis and encephalitis by Culex mosquitoes, malaria by Anopheles mosquitoes, and dengue fever by Aedes mosquitoes. The use of chemicals in repelling and killing mosquitoes, is very harmful to the environment and also causes resistance in mosquitoes. This study aims to test the potential of eco-enzyme as a mosquito repellent, with basic ingredients of orange peel and papaya leaves. This type of research is an experimental study that uses Complete Randomized Design (RAL) in 2x5 Factorial. The concentrations used in this study were 100%, 2.5%, 5%, 10%, and 20%. Data were analyzed using Anova and DNMRT 5% follow-up test. In the research conducted, the results were obtained, namely in the trial of lime ecoenzyme combination of papaya leaves at a concentration of 100%, 2.5%, 5%, 10% and 20% there were no mosquitoes perched on the test arm, then the papaya leaf ecoenzyme trial there was 1 mosquito that perched.